Lateral Orbitofrontal Cortical Modulation on the Medial Prefrontal Cortex-Amygdala Pathway: Differential Regulation of Intra-Amygdala GABA(A) and GABA(B) Receptors - Chang, Chun-hui (Int J Neuropsychopharmacol, 2017)
BACKGROUND: The basolateral complex of the amygdala receives inputs from neocortical areas, including the medial prefrontal cortex and lateral orbitofrontal cortex. Earlier studies have shown that lateral orbitofrontal cortex activation exerts an inhibitory gating on medial prefrontal cortex-amygdala information flow. Here we examined the individual role of GABA(A) and GABA(B) receptors in this process. METHODS: In vivo extracellular single-unit recordings were done in anesthetized rats. We searched amygdala neurons that fire in response to medial prefrontal cortex activation, tested lateral orbitofrontal cortex gating at different delays (lateral orbitofrontal cortex-medial prefrontal cortex delays: 25, 50, 100, 250, 500, and 1000 milliseconds), and examined differential contribution of GABA(A) and GABA(B) receptors with iontophoresis. RESULTS: Relative to baseline, lateral orbitofrontal cortex stimulation exerted an inhibitory modulatory gating on the medial prefrontal cortex-amygdala pathway and was effective up to a long delay of 500 ms (long-delay latencies at 100, 250, and 500 milliseconds). Moreover, blockade of intra-amygdala GABA(A) receptors with bicuculline abolished the lateral orbitofrontal cortex inhibitory gating at both short- (25 milliseconds) and long-delay (100 milliseconds) intervals, while blockade of GABA(B) receptors with saclofen reversed the inhibitory gating at long delay (100 milliseconds) only. Among the majority of the neurons examined (8 of 9), inactivation of either GABA(A) or GABA(B) receptors during baseline did not change evoked probability per se, suggesting that local feed-forward inhibitory mechanism is pathway specific. CONCLUSIONS: Our results suggest that the effect of lateral orbitofrontal cortex inhibitory modulatory gating was effective up to 500 milliseconds and that intra-amygdala GABA(A) and GABA(B) receptors differentially modulate the short- and long-delay lateral orbitofrontal cortex inhibitory gating on the medial prefrontal cortex-amygdala pathway.